Enhanced understanding of cinnamaldehyde’s therapeutic potential in osteoarthritis through bioinformatics and mechanistic validation of its anti-apoptotic effect - Sheng, Yueyang; Zhai, Ruiqing; Li, Shan; Wang, Xinyu; Wang, Ying; Cui, Zhengguo; Wang, Chao; Wang, Qianqian; Zhang, Yanzhuo; Wu, Chengai (Frontiers in Medicine, 2024)
Introduction Osteoarthritis (OA) is a globally prevalent joint disorder affecting approximately 240 million individuals worldwide. Cinnamaldehyde, known for its broad anti-inflammatory and anti-aging effects across various cell types, has not been investigated for its potential impact on apoptosis in OA chondrocytes. Methods To explore the effectiveness of cinnamaldehyde in mitigating knee osteoarthritis by reducing chondrocyte apoptosis, bioinformatics analysis was first conducted to identify apoptosis-associated differentially expressed genes (APDEGs). Gene expression datasets GSE55235 and GSE114007 were analyzed using weighted gene co-expression network analysis (WGCNA). Gene modules of interest were cross-referenced with APDEGs to identify those specific to OA. LASSO regression analysis was employed to build a risk model, and this model, along with datasets GSE114007, GSE55457, and GSE12021, was validated using ROC analysis. Cellular experiments and blood analyses from OA patients were performed to evaluate the effects of cinnamaldehyde on apoptosis-related gene expression. Results Cinnamaldehyde administration was found to rectify the abnormal expression of key apoptosis-related genes in OA patients. Specifically, cinnamaldehyde may affect knee osteoarthritis by regulating apoptosis-related genes such as ZFAND5, BCL6, ELL2, FOSL2, MARCKS, and SGCD. Additionally, three novel apoptotic targets in OA chondrocytes—ZFAND5, ELL2, and SGCD—were identified. Discussion These findings provide significant theoretical support for the clinical use of cinnamaldehyde in OA treatment. The discovery of novel apoptotic targets presents new therapeutic possibilities for future OA interventions.